Tingkat Nyeri dan Kualitas Hidup pada Pasien Endometriosis Setelah Pemasangan Implan Levonorgestrel - Ramadhani Sheba Arifin; Dwi Retna Lestari; Agus Sujono; Eka Rusdianto Gunardi (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Endometriosis is characterized by the presence of tissue resembling endometrial glands that grows outside the uterus. This condition triggers a chronic inflammatory reaction which results in pain and adhesions. Pain in endometriosis patients is the most common complaint experienced and has an impact on quality of life. Hormonal therapy to treat pain in endometriosis patients, one of which can use progesterone. The Levonorgestrel implant is a long-term contraceptive method that contains the hormone progesterone with high effectiveness. The aim of the study was to assess the efficacy of levonogestrel implants in improving pain and quality of life in endometriosis patients. This research is descriptive qualitative. A total of 10 subjects who met the inclusion criteria had implants installed and were followed for 6 months after LNG implant insertion. Pain improvement was assessed using VAS scores and quality of life with the EHP-30 questionnaie.